2020
DOI: 10.1021/acs.jafc.0c00245
|View full text |Cite
|
Sign up to set email alerts
|

High-Meat-Protein High-Fat Diet Induced Dysbiosis of Gut Microbiota and Tryptophan Metabolism in Wistar Rats

Abstract: Meat-diet-induced changes in gut microbiota are often accompanied with the development of various metabolic and inflammatory disorders. The exact biochemical mechanism underlying these effects is not well elucidated. This study aims to evaluate how meat proteins in high-fat diets affect tryptophan metabolism in rats. The high-chicken-protein (HFHCH) or high-pork-protein (HFHP) diets increased levels of skatole and indole in cecal and colonic contents, feces, and subcutaneous adipose tissue. The HFHCH and HFHP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 59 publications
6
43
0
Order By: Relevance
“…Meanwhile, taxa of two predominantly butyrate-producing genus, Faecalibacterium and Ruminococcus, are also reported significantly more prevalent in obese individuals than in non-obese individuals (Maniar et al, 2019). As shown in the cecum and colon of rats (Shi et al, 2020), the increase in the Family XIII AD3011 group may be involved in the production of skatole and indole. Moreover, the families Lachnospiraceae, Clostridia, and Ruminococcaceae, and genera Ruminiclostridium, Blautia, and Butyrivibrio, have been suggested as high fat diet-dependent gut taxa and are likely associated with lipid metabolism (Lin et al, 2016;Zietak et al, 2016;Kong et al, 2019;Hou et al, 2020).…”
Section: Discussionmentioning
confidence: 89%
“…Meanwhile, taxa of two predominantly butyrate-producing genus, Faecalibacterium and Ruminococcus, are also reported significantly more prevalent in obese individuals than in non-obese individuals (Maniar et al, 2019). As shown in the cecum and colon of rats (Shi et al, 2020), the increase in the Family XIII AD3011 group may be involved in the production of skatole and indole. Moreover, the families Lachnospiraceae, Clostridia, and Ruminococcaceae, and genera Ruminiclostridium, Blautia, and Butyrivibrio, have been suggested as high fat diet-dependent gut taxa and are likely associated with lipid metabolism (Lin et al, 2016;Zietak et al, 2016;Kong et al, 2019;Hou et al, 2020).…”
Section: Discussionmentioning
confidence: 89%
“…On the other hand, Prevotella 9 , Dialister , Faecalibacterium , Megamonas , and Prevotella 2 were more abundant in the feces of chicken-eaters. Such a difference could be attributed to dietary structure that is more complex than a strictly controlled diet in our previous rat study 13 . In that study, chicken and pork protein diets increased the abundance of Lactobacillus , the Family XIII AD3011 group , and Desulfovibrio in rat large intestine relating to the production of skatole and indole 13 .…”
Section: Discussionmentioning
confidence: 83%
“…Many studies have been focused on the effects of meat consumption on the composition of gut microbiota, however, only few studies investigated an impact of meat consumption on tryptophan metabolites. In a previous study, we found that a high fat high chicken or pork protein diet increased the abundance of gut microbiota associated with skatole and indole production in Wistar rats 13 . In the present study, we investigated the differences in composition of gut microbiota, tryptophan metabolites and SCFAs in feces in volunteers who frequently consume chicken or pork products.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…However, HPD showed a reduction in fecal butyrate concentration in a repetitive manner. The intake of high-fat and high-protein diets can lead to a dysfunction in the intestinal microbiota; its metabolite biosynthesis may lead to an imbalance, which subsequently causes intestinal inflammation that may further lead to IBD ( Shi et al., 2020 ). Caspase recruitment domain-containing protein 9 is one among many IBD-susceptible genes, promoting the recovery of colitis by activating the interleukin-22 pathway ( Lamas et al., 2016 ).…”
Section: Protein/amino Acid Metabolites In the Progression Of Gastrointestinal Diseasesmentioning
confidence: 99%